Gender inequality, and adolescent fatherhood in two indigenous communities in Chiapas, Mexico - Vázquez-Solís, Ezequiel (2023)
Introduction: Teenage paternity has been considered an important social problem that has been recently studied from the sociocultural construction of masculinities and gender inequality. This work contributes to documenting the experience of adolescent fatherhood in two Ch'ol and Tseltal indigenous rural communities in the state of Chiapas, Mexico. Methodology: The study was conducted through a qualitative approach, the data collection technique consisted of semi-structured interviews and the selection of participants was through the linear snowball technique. Twenty-five complete interviews were carried out in two stages, 13 in each locality, of which 16 were with children under 20 years of age who were fathers and mothers in adolescence, five with men between 24 and 40 years old, and four with men aged 50 and over. Results: Adolescent fatherhood is associated with the construction of masculinities, supported by traditional sociocultural norms such as payment for the bride, polygyny, and the traffic of women. Teenage pregnancy is associated with the importance of fatherhood for men despite the resistance of women to unite and get pregnant early. Conclusions: There are some conditions that facilitate the occurrence of adolescent fatherhood, but not as an individual, isolated phenomenon, but rather in the context of (economic) production, family structures and the subordination of women, which have remained despite some generational social changes.